Modeling the distribution of the Southern yellow-cheeked gibbon (Nomascus gabriellae) using maxent - Nhung, Cao Thi Hong; Duc, Le Minh; Anh, Nguyen Tuan (Vietnam Journal of Science and Technology, 2021)
The Southern Yellow-cheeked Gibbon (Nomascus gabriellae) is an endangered species found only in a small region of Indochina, and its populations have declined in most known sites. In this study, we use Maxent, a robust and widely used species distribution modeling approach, to predict the current and future distributions of the Southern Yellow-cheeked Gibbon over its entire range based on an extensive review of published records. In total, we compile and provide a comprehensive set of known distribution records of the species from Cambodia, Laos, and Vietnam. The model results show that N. gabriellae potentially occurs in much of area around the Central Highlands in both Vietnam and Cambodia sides and the southern end of Laos. Our study suggests that protected areas in this region will play a key role in conservation actions for the gibbons. In addition, the distribution of the gibbon in future climate conditions, even in the best-case scenario, is likely to shrink significantly, as the species would have to move upwards to higher elevations. Under such impact, the populations will become more fragmented and restricted to a few areas with higher elevations. Our study also confirms that the climatic difference in distribution ranges may not be fully responsible for the speciation and biogeography of the N. annamensis/gabriellae complex